Fluorescent Probes with Förster Resonance Energy Transfer Function for Monitoring the Gelation and Formation of Nanoparticles Based on Chitosan Copolymers - Igor D. Zlotnikov; Ivan V. Savchenko; Elena V. Kudryashova (Journal of Functional Biomaterials, 2023)
Nanogel-forming polymers such as chitosan and alginic acid have a number of practical applications in the fields of drug delivery, food technology and agrotechnology as biocompatible, biodegradable polymers. Unlike bulk macrogel formation, which is followed by visually or easily detectable changes and physical parameters, such as viscosity or turbidity, the formation of nanogels is not followed by such changes and is therefore very difficult to track. The counterflow extrusion method (or analogues) enables gel nanoparticle formation for certain polymers, including chitosan and its derivatives. DLS or TEM, which are typically used for their characterization, only allow for the study of the already-formed nanoparticles. Alternatively, one might introduce a fluorescent dye into the gel-forming polymer, with the purpose of monitoring the effect of its microenvironment on the fluorescence spectra. But apparently, this approach does not provide a sufficiently specific signal, as the microenvironment may be affected by a big number of various factors (such as pH changes) including but not limited to gel formation per se. Here, we propose a new approach, based on the FRET effect, which we believe is much more specific and enables the elucidation of nanogel formation process in real time. Tryptophan-Pyrene is suggested as one of the donor–acceptor pairs, yielding the FRET effect when the two compounds are in close proximity to one another. We covalently attached Pyrene (the acceptor) to the chitosan (or PEG-chitosan) polymeric chain. The amount of introduced Pyrene was low enough to produce no significant effect on the properties of the resulting gel nanoparticles, but high enough to detect the FRET effect upon its interaction with Trp. When the Pyr-modified chitosan and Trp are both present in the solution, no FRET effect is observed. But as soon as the gel formation is initiated using the counterflow extrusion method, the FRET effect is easily detectable, manifested in a sharp increase in the fluorescence intensity of the pyrene acceptor and reflecting the gel formation process in real time. Apparently, the gel formation promotes the Trp-Pyr stacking interaction, which is deemed necessary for the FRET effect, and which does not occur in the solution. Further, we observed a similar FRET effect when the chitosan gel formation is a result of the covalent crosslinking of chitosan chains with genipin. Interestingly, using ovalbumin, having numerous Trp exposed on the protein surface instead of individual Trp yields a FRET effect similar to Trp. In all cases, we were able to detect the pH-, concentration- and temperature-dependent behaviors of the polymers as well as the kinetics of the gel formation for both nanogels and macrogels. These findings indicate a broad applicability of FRET-based analysis in biomedical practice, ranging from the optimization of gel formation to the encapsulation of therapeutic agents to food and biomedical technologies.